2022
DOI: 10.1128/jvi.00523-22
|View full text |Cite
|
Sign up to set email alerts
|

Modified E2 Glycoprotein of Hepatitis C Virus Enhances Proinflammatory Cytokines and Protective Immune Response

Abstract: Hepatitis C virus (HCV) E2-CD81 binding dampens protective immune response. We have identified that an alteration of amino acids in the front layer of soluble E2 (sE2) disrupts CD81 interaction and alters the cytokine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…However, the effect of MF59 appeared to be reduced in the immunized volunteers, as suggested from IL-10 induction, and an undetectable level of IL-12. A similar induction of IL-10, but not IL-12, was observed using human macrophages in our subsequent in vitro study using purified recombinant E2 glycoprotein 7 , and reinforced in a recent study using in vitro samples, and vaccinated mice 8 . HCV entry into hepatocytes is facilitated by binding with CD81, which represents a major site of vulnerability for consideration in vaccine design.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the effect of MF59 appeared to be reduced in the immunized volunteers, as suggested from IL-10 induction, and an undetectable level of IL-12. A similar induction of IL-10, but not IL-12, was observed using human macrophages in our subsequent in vitro study using purified recombinant E2 glycoprotein 7 , and reinforced in a recent study using in vitro samples, and vaccinated mice 8 . HCV entry into hepatocytes is facilitated by binding with CD81, which represents a major site of vulnerability for consideration in vaccine design.…”
Section: Introductionsupporting
confidence: 82%
“…We examined whether impairing the E2-CD81 interaction by using modified E2 with point mutations and the insertion of a glycosylation site (F442NYT) altered cytokine parameters associated with an improved proinflammatory response. Soluble ectodomain regions of E1/E2 F442NYT delivered as an mRNA-LNP candidate vaccine exhibited improved T-helper cell function, neutralizing antibody response, and afforded robust cellular immunity in mice during a surrogate challenge infection using recombinant vaccinia virus expressing HCV E1-E2-NS2 (aa134–966) 8 . Our findings could potentially lead to the further development of a multi-genotype mRNA- LNP HCV vaccine approach to promote protective humoral and cellular immune responses for future human use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular immune responses play an important role in the pathogenesis of chronic hepatitis C [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. The secretion of cytokines such as interleukin (IL)-2, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α by CD4 + and CD8 + T lymphocytes activates antiviral mechanisms [ 76 ].…”
Section: Mechanism Of Acute Exacerbation and Alanine Aminotransferase...mentioning
confidence: 99%
“…Hiura et al also reported a case of severe acute hepatitis C and delayed antibody production due to rituximab [ 75 ]. These reports suggest the presence of stronger antibody-mediated immune pressure on HCV infection [ 89 , 90 ]. As innate and acquired immune responses play a role in the control of HCV replication [ 76 , 91 , 92 , 93 ] in the pathogenesis of the acute exacerbation and hepatic flare of chronic HCV infection, cellular, as well as humoral, immunological responses may be involved ( Figure 1 ).…”
Section: Mechanism Of Acute Exacerbation and Alanine Aminotransferase...mentioning
confidence: 99%